Multifunctional Nanoplatform-Mediated Chemo-Photothermal Therapy Combines Immunogenic Cell Death with Checkpoint Blockade to Combat Triple-Negative Breast Cancer and Distant Metastasis - Zhu H; Yang K; Yao H; Chen X; Yan S; He Y; Cao Y; Luo J; Wang D (International Journal of Nanomedicine, 2023)
Hui Zhu,1,2 Ke Yang,3 Huan Yao,1 Xueying Chen,1 Shujin Yan,1,2 Yiman He,1,2 Yang Cao,2 Jie Luo,1 Dong Wang1 1Department of Ultrasound, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Chongqing Key Laboratory of Ultrasound Molecular Imaging, Chongqing Medical University, Chongqing, People’s Republic of China; 3Pediatric Research Institute, Children’s Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Jie Luo; Dong Wang, Department of Ultrasound, The First Affiliated Hospital of Chongqing Medical University, 1 Youyi Road, Yuzhong District, Chongqing, 400042, People’s Republic of China, Email luojie1983@cqmu.edu.cn; wangdong4429@cqmu.edu.cnBackground: Breast cancer has become the most common cancer in women. Compare with other subtypes of breast cancer, triple-negative breast cancer (TNBC) is more likely to relapse and metastasize. Highly effective therapeutic strategies are desperately needed to be explored. In this study, a multifunctional nanoplatform is expected to mediate chemo-photothermal therapy, which can combine immunogenic cell death with checkpoint blockade to combat TNBC and distant metastasis.Methods: Poly (lactic acid-glycolic acid)-Poly (ethylene glycol) (PLGA-PEG) nanoparticles (NPs), a type of polymeric NPs, loaded with IR780, a near-infrared (NIR) dye, and doxorubicin (DOX) as the chemotherapeutic drug, were assembled by an improved double emulsification method (designated as IDNPs). The characterization, intracellular uptake, biosafety, photoacoustic (PA) imaging performance, and biodistribution of IDNPs were studied. Chemo-photothermal therapeutic effect and immunogenic cell death (ICD) were evaluated both in vitro and in vivo. The potency of chemo-photothermal therapy-triggered ICD in combination with anti-PD-1 immune checkpoint blockade (ICB) immunotherapy in eliciting immune response and treating distant tumors was further investigated.Results: IR780 and DOX were successfully loaded into PLGA-PEG to form the IDNPs, with size of 243.87nm and Zeta potential of − 6.25mV. The encapsulation efficiency of IR780 and DOX was 83.44% and 5.98%, respectively. IDNPs demonstrated remarkable on-site accumulation and PA imaging capability toward 4T1 TNBC models. Chemo-photothermal therapy demonstrated satisfactory therapeutic effects both in vitro and in vivo, and triggered ICD efficiently. ICD, in combination with anti-PD-1, provoked a systemic antitumor immune response against distant tumors.Conclusion: Multifunctional IDNPs were successfully synthesized to mediate chemo-photothermal therapy, which combines immunogenic cell death with checkpoint blockade to combat TNBC and distant metastasis, showing great promise preclinically and clinically.Keywords: immunogenic cell death, immunotherapy, checkpoint blockade, chemo-photothermal therapy, triple-negative breast cancer